Harmonization of Modern Law and Customary Law in Fair Criminal Law Enforcement - Ino Susanti; Agus Marzuki; Tahura Malagano; Tora Yuliana; Dina Haryati Sukardi (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the harmonization of modern criminal law and customary law to achieve fair criminal law enforcement through a case study of the settlement of minor criminal offenses using customary mechanisms in Lampung Province. Methodology: This study employs an empirical juridical method with a qualitative approach. Data were collected through a literature review, analysis of statutory regulations, judicial decisions, and documentation of criminal dispute resolution practices involving Lampung’s customary institutions. Results: The findings show that Lampung customary law remains effective in resolving minor criminal cases through restorative justice, integrating customary values with national criminal law while ensuring legal certainty and human rights protection. The study concludes that legal harmonization strengthens substantive justice, public trust, and social harmony. This study is limited to minor criminal disputes in Lampung Province. Conclusions: This study concludes that the harmonization of modern criminal law and customary law can strengthen substantive justice, improve public trust in law enforcement, and promote sustainable social harmony. Customary approaches can serve as complementary mechanisms within the national criminal justice system, particularly for minor offenses. Limitations: This study is limited to customary criminal dispute resolution practices in Lampung Province and primarily focuses on minor criminal offenses, which may restrict the generalizability of the findings to other regions and types of crimes. Contributions: This study contributes to the development of criminal law by providing an empirical model for integrating customary law into restorative justice policies and supporting future legal reforms in Indonesia.